Inverse problem of life cycle assessment (LCA): its application in designing for environment (DfE) = Zagadnienie odwrotne oceny cyklu życia (LCA): zastosowanie w projektowaniu dla środowiska (DfE) - Rybaczewska-Błażejowska, Magdalena; Masternak-Janus, Aneta; Gierulski, Wacław (Zielona Góra: Faculty of Economics and Management Press)
The inverse problem of life cycle assessment, used in designing for environment, is about determining the optimal values of environmental inputs that provide the required environmental impacts. The notion of the inverse problem of life cycle assessment is explained here using a case study of a coffee machine (abstract model SimaPro, based on models Sima and Pro described in SimaPro 8.1 software). The dependencies between input and output signals were defined by nonlinear functions of several variables. Next, linearization was used and coefficient aki was calculated.
Keywords: projektowanie dla środowiska; DfE; zagadnienie odwrotne; ocena cyklu życia (istnienia); LCA; design for environment; inverse problem; life cycle assessment (LCA)